2020
DOI: 10.1101/2020.03.28.013052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introductory gestures before songbird vocal displays are shaped by learning and biological predispositions

Abstract: 9Introductory gestures are present at the beginning of many animal displays. For example, lizards start 10 their head-bobbing displays with introductory push-ups and animal vocal displays begin with 11 introductory notes. Songbirds also begin their vocal displays by repeating introductory notes (INs) 12 before producing their learned song and these INs are thought to reflect motor preparation. Between 13 individuals of a given species, the acoustic structure of INs and the number of times INs are repeated 14 b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…3B shows spectrograms of tutor song and songs of two juveniles; Fig. 3C; n=6 birds with video and n=10 birds with only audio playbacks from Kalra et al (Kalra et al, 2021)). These results suggested that the visual presence of an adult bird, albeit on a screen, does not improve copying accuracy and is supported by similar results from a recent study (Varkevisser et al, 2022a).…”
Section: Methods For Closed Loop Control Of the Animationmentioning
confidence: 99%
See 4 more Smart Citations
“…3B shows spectrograms of tutor song and songs of two juveniles; Fig. 3C; n=6 birds with video and n=10 birds with only audio playbacks from Kalra et al (Kalra et al, 2021)). These results suggested that the visual presence of an adult bird, albeit on a screen, does not improve copying accuracy and is supported by similar results from a recent study (Varkevisser et al, 2022a).…”
Section: Methods For Closed Loop Control Of the Animationmentioning
confidence: 99%
“…Songs were analysed as described earlier (Kalra et al, 2021; Rajan and Doupe, 2013; Rao et al, 2019), using custom-written scripts on MATLAB (MathWorks). Briefly, songs were first segmented into syllables based on an amplitude threshold.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations